Nosocomial infections in intensive care - Hammond, Janet Margaret Justine (Division of Medical Microbiology, 2017)
The objectives of this thesis are : 1) To provide a review of the literature on the significance, pathogenesis, diagnosis and management of secondary infections in the Intensive Care Unit. 2) To present the findings of a study of the technique of selective parenteral and enteral antisepsis regimen (SPEAR) in the patient population of the Respiratory ICU at Groote Schuur Hospital, aimed at reducing the incidence of secondary infection and, further to evaluate the study in terms of the effect of SPEAR on the incidence of secondary infection and its influence on the mortality due to secondary infection. 3) To present the findings of the effect of SPEAR on patient bacterial colonisation in the ICU, and to evaluate its longterm influence on the microbial flora of the ICU.